A247 RECOGNITION OF LYNCH SYNDROME AMONGST NEWLY DIAGNOSED COLORECTAL CANCER AT ST. PAUL'S HOSPITAL. (1st March 2018) - Pi, S; Nap-Hill, E; Telford, J J; Enns, R A
Abstract: Background: Lynch syndrome (LS) is the most common cause of inherited colorectal cancer (CRC). Numerous strategies exist for identifying patients with LS. In British Columbia, clinical criteria (Amsterdam II criteria, Revised Bethesda guidelines, or the BC Cancer Agency's Hereditary Cancer Program (BCCA HCP) criteria) are first used to determine who should undergo further first-line testing in the form of microsatellite instability (MSI) testing or immunohistochemistry (IHC) staining. Limitations exist with this strategy, including ease of access and, consequently, LS is thought to be under-recognized. Aims: The purpose of this study is to investigate whether LS is truly under-recognized when compared to the reported prevalence and, if so, identify what factors are contributing to this. Methods: A retrospective chart review of all CRC diagnosed at St. Paul's Hospital from 2010–2013 was conducted. The list of all CRC was obtained through St. Paul's Hospital Department of Pathology after ethics approval. Results: Of 246 patients who met inclusion criteria, 96% (235 of 246) had a family history available in their chart. 76% (83 of 109) with a family history of malignancy were unable to recall the specific malignancy or age of diagnosis. 18% (45 of 235) were apparently only asked about a history of gastrointestinal related malignancy and 26% (65 of 246) met at least one of the three clinical criteria but only 21% (13 of 63) received further investigation in the form of MSI testing, IHC staining, or BCCA HCP referral. When compared to the entire study population, patients who received further testing had a statistically significant younger age (66 vs. 49, p<0.01), past medical history of malignancy (0.16 vs. 0.38, p=0.03) and family history of malignancy (0.46 vs. 0.92, p<0.01). Only 1.6% (4 of 246) were found to have LS compared to the reported prevalence of 2–5% of all CRC. Conclusions: This data supports our hypothesis that LS is under-recognized. Contributing factors include poor recollection of family histories by patients, incomplete family histories by physicians, and under-investigation for those at risk of LS which we speculate is, in part, due to difficulty accessing MSI-testing and IHC staining. The present system of reliance on histories and patients to report their family histories appear to be inadequate and need modification. A system such as that suggested by the latest AGA Guidelines where all cancers are universally tested needs implementation to minimize the risk of missing LS patients. Funding Agencies: St. Paul's Hospital GI Research Institute